On the Security of a Pairing-Free Certificateless Signcryption Scheme. (7th September 2017) - Zhang, Jianhong; Mao, Jian
Abstract: Unforgeability is an important security property in signcryption. Recently, Yu et al. proposed a pairing-free and secure certificateless signcryption scheme and demonstrated their scheme was provably secure in the random oracle model. Unfortunately, in this letter, we show their scheme is insecure against the malicious KGC and the malicious sender through proposing two concrete attacks.